2009
DOI: 10.1007/978-3-642-03658-3_52
|View full text |Cite
|
Sign up to set email alerts
|

Designing Laser Gesture Interface for Robot Control

Abstract: Abstract.A laser pointer can be a powerful tool for robot control. However, in the past, their use in the field of robotics has been limited to simple target designation, without exploring their potential as versatile input devices. This paper proposes to create a laser pointer-based user interface for giving various instructions to a robot by applying stroke gesture recognition to the laser's trajectory. Through this interface, the user can draw stroke gestures using a laser pointer to specify target objects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 16 publications
0
45
0
Order By: Relevance
“…Laser Gesture [1] is a system for operating mobile robots by using a laser pointer and ceiling camera for detecting pointer. It is convenient but not applicable for complex motion and also faces laser safety issues.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Laser Gesture [1] is a system for operating mobile robots by using a laser pointer and ceiling camera for detecting pointer. It is convenient but not applicable for complex motion and also faces laser safety issues.…”
Section: Related Workmentioning
confidence: 99%
“…Recent approaches for direct selection of the target device are based on hand gestures, and laser pointers [1]. Another approach for device selection is using a touch screen with camera captured image [2] [4].…”
Section: Introductionmentioning
confidence: 99%
“…Lasers incur relatively lower cost and higher functional flexibility (Brogardh, 2009); lightweight, accurate, and highly reliable (Ishii, Zhao, Inami, Igarashi, & Imai, 2009); can have wider bandwidth, lower power requirements, and increased potential for covert data links in comparison with radio-based systems (Sofka, Nikulin, Skormin, Hughes, & Legare, 2009). Lasers can enable better tracking (Luber, Tipaldi, & Arras, 2011) and have inherent precision which results in better functionalities for precise collaboration.…”
Section: Overview: Advantages and Opportunities In Using Lasers For Cmentioning
confidence: 97%
“…A laser pointer provides a powerful alternative as a user interface for robot control. It is inexpensive, lightweight, points accurately, and is reliably recognized (Ishii et al, 2009). Previous research showed that a laser pointer can be useful for providing target designation for a picking-up robot (Kemp, Anderson, Nguyen, & Xu, 2008) and developed for a button-pushing robot (Suzuki, Ohya, & Yuta, 2005).…”
Section: Collaboration Support Function 1: Targetingmentioning
confidence: 98%
“…TouchMe [10] applies direct-manipulation techniques for remote robot control using video see-through AR and a touch-screen interface. Ishii et al [15] enable real-world pointing and gesturing for robot control, using a tracked laser with projected visual feedback.…”
Section: Ar Interfaces For Control Of Physical Objectsmentioning
confidence: 99%